eGFRCystatin C, difference between eGFRCystatin C and eGFRCre and heart failure: Insight from the NHANES 2001–2002 and Mendelian randomization analysis - Zhiyu Gu; Rui Zhang; Weihong Chang; Hongxuan Fan; Zixuan Dou; Peng Liu; Aman Liu; Boda Zhou (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Aim: Estimated glomerular filtration rate (eGFR) derived from Cystatin C (eGFRCystatin C), and the difference between Cystatin C and creatinine based eGFR (eGFRdiff) has been suggested to be associated with cardiovascular disease. However, the association between eGFRCystatin C,eGFRdiff and heart failure (HF) risk has not been elucidated in a relatively healthy cohort. Methods: We used cohort study data from the NHANES 2001–2002. Mendelian randomization (MR) study used GWAS data from 437,846 European participants. The exposures are eGFRCystatin C & eGFRdiff, outcome is self reported heart failure. Weighted multivariable-adjusted logistic regression and Kaplan-Meier survival analysis was used in corhort study. Inverse variance weighted (IVW) was applied in MR study. Results: The cohort study included 2155 participants. Importantly, we simplified eGFRdiff classification into ≥0 and < 0, and found that eGFRdiff≥0 was associated with 52 % reduction of HF risk (OR 0.48, [95 % CI, 0.29–0.80], p = 0.005). We also found that 1 ml/min/1.73 m2 of eGFRCystatin C had a significant negative association with HF after adjusting for covariates. Interestingly, we showed a non-linear association between eGFRCystatin C and HF, eGFRdiff and HF. In participants without know HF, during a median follow-up of 17.3 years, those in the low eGFRCystatin C or low eGFRdiff groups showed significantly poorer survival. Moreover, MR analysis found genetic predisposition to cystatin C was significantly associated with an increased risk of HF. Conclusion: Both decreased eGFRCystatin C and eGFRdiff levels were associated with heart failure and poor survival, but the latter seems more obvious.